THE IMPORTANCE OF CULTURE IN TEACHING FOREIGN LANGUAGES - Bozorboyeva, Sanobar (FILOLOGIYA UFQLARI JURNALI, 2022)
Culture, conveyed from one generation to another, defines the identity of a society and distinguishes it from other societies. Nostrand defines culture as the "ground of meaning", the codes of behavior and characteristics of a society. Brooks defines culture as “the sum of all the learned and shared elements that characterize a societal group.” “Language is a vital constituent of culture”. Robinett concurs with the view that culture and language cannot be separated.